Functional layer with adhesive layer, laminate and use thereof

JP7630994B2Active Publication Date: 2025-02-18MITSUI CHEMICALS INC +1

Patent Information

Application Number
JP2020549377
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-26
Filing Date
2019-09-26
Publication Date
2025-02-18
Estimated Expiration
2039-09-26

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、機能性層と基材との密着性、さらにアニール時の外周端部における密着性に優れる接着層付き機能性層を提供することができる。 さらに、本発明によれば、機能性層と基材との密着性、さらにアニール時の外周端部における密着性に優れるとともに、レンズの外周加工時における外周端部の加工残りの発生が抑制される積層体も提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630994000001
    Figure 0007630994000001
  • Figure 0007630994000002
    Figure 0007630994000002
  • Figure 0007630994000003
    Figure 0007630994000003
Patent Text Reader

Abstract

The functional layer with an adhesive layer of the present invention comprises a functional layer and a curable adhesive layer AD2 arranged on at least a portion of the surface of the functional layer, and the curable adhesive layer AD2 satisfies all of the following requirements (1) and (2). (1) At 25°C, place a 32g steel ball on the adhesive surface of the curable adhesive layer AD2, hold it there for 10 seconds, then gradually tilt the glass plate until the angle at which the steel ball begins to roll is 5 degrees or less. (2) After curing at 90°C for 2 hours, the ratio of the plastic deformation amount b to the elastic deformation amount a (b / a) at 25°C under a load of 0.1 mN is 0.01 to 100.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a functional layer with an adhesive layer, a laminate, and uses thereof. [Background technology]

[0002] Polarized lenses can prevent the transmission of reflected light. Therefore, they are used to protect the eyes by blocking strong reflected light outdoors, such as at ski resorts or fishing, and to ensure safety by blocking reflected light from oncoming vehicles when driving a car.

[0003] Patent Document 1 discloses a plastic polarized lens that is made of a plastic lens substrate and a polyvinyl alcohol-based polarized film. The document describes that the lens substrate and the polarized film are bonded together with an epoxy resin or the like.

[0004] Patent Document 2 discloses a method for pressing a preheated flat polarizing film onto the convex surface of a lens substrate while pressing it with a pad, and adhering the film onto the convex surface of the lens substrate via a pressure-sensitive adhesive, and a polarized lens obtained by the method. The document discloses that the pressure-sensitive adhesive is selected from a polyacrylate-based compound and a styrene-based block copolymer. Patent Document 3 discloses a lens in which a first layer and a second layer are bonded together with an adhesive strength measured by a predetermined method.

[0005] Patent Document 4 discloses a plastic polarized lens having a polarized film made of polyethylene terephthalate on the surface of a plastic material. This document describes the manufacture of polarized lenses by injection molding, and does not disclose a technique for bonding a polarized film to a plastic material.

[0006] Patent Document 5 discloses a plastic polarized lens having a thiourethane resin layer on at least one surface of a polarized film made of thermoplastic polyester shaped under specified temperature conditions. Patent Document 6 discloses a polarized lens having a lens substrate on one surface of a thermoplastic resin film that is shaped in a non-contact state by a molding device. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 9-258009 [Patent Document 2] Special Publication No. 2009-527783 [Patent Document 3] US Publication No. 2017 / 0139230 [Patent Document 4] Special Publication No. 2003-533719 [Patent Document 5] International Publication No. 2009 / 098886 [Patent Document 6] International Publication No. 2017 / 146201 Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the conventional techniques described in Patent Documents 1 to 6, there is room for improvement in the adhesion between a functional layer such as a polarizing layer and a substrate, particularly in areas with a small radius of curvature. Furthermore, there is room for improvement in the adhesion at the outer periphery during annealing. Furthermore, the present inventors have conducted research and found a new problem in that processing residue occurs at the outer periphery of the lens during edging (outer periphery processing) in the lens manufacturing process. This problem is not limited to cases where the substrate is a lens, but is considered to be a problem that occurs when a functional layer such as a polarizing layer is bonded to a substrate and the outer periphery is processed, particularly when the substrate has a portion with a small radius of curvature. The residual processing refers to the state in which the functional resin film, such as the polarizing film, remains on the outer edge of the lens after the grinding and polishing (cutting) process of the outer periphery processing. This residual processing is thought to occur because the functional resin film is more difficult to cut and cut during the grinding and polishing (cutting) process than the lens substrate.

[0009] That is, a first object of the present invention is to provide a functional layer with an adhesive layer that has excellent adhesion between the functional layer and a substrate, and further has excellent adhesion at the outer peripheral edge during annealing.

[0010] Furthermore, a second object of the present invention is to provide a laminate that has excellent adhesion between a functional layer and a substrate, and also excellent adhesion at the outer peripheral edge during annealing, and that suppresses processing residue at the outer peripheral edge of the lens during peripheral processing in the lens manufacturing process. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that at least one of the above problems can be solved by using a curable adhesive layer having specific properties, and have completed the present invention.

[0012] That is, the present invention can be shown as follows. [1] Functional layer; a curable adhesive layer AD2 disposed on at least a portion of a surface of the functional layer; Equipped with The curable adhesive layer AD2 is a functional layer with an adhesive layer that satisfies all of the following requirements (1) and (2). (1) At 25°C, a 32g steel ball is placed on the adhesive surface of the curable adhesive layer AD2, and after holding it there for 10 seconds, the glass plate is gradually tilted until the angle at which the steel ball begins to roll is 5 degrees or less. (2) After curing at 90°C for 2 hours, the ratio of the amount of plastic deformation b to the amount of elastic deformation a at 25°C under a load of 0.1 mN (b / a) is 0.01 to 100. [2] The adhesive layer-attached functional layer according to [1], wherein the curable adhesive layer AD2 satisfies the following requirement (3): (3) After curing at 90°C for 2 hours, the dynamic hardness (DHT115-2) after unloading a 0.1 mN load at 25°C is 0.01 to 5000 [3] The adhesive layer-attached functional layer according to [1] or [2], wherein the curable adhesive layer AD2 satisfies the following requirement (4): (4) The storage modulus at 25°C after curing at 90°C for 2 hours is 0.5 MPa or more and 1000 MPa or less. [4] The functional layer with an adhesive layer according to any one of [1] to [3], wherein the amount of plastic deformation b is greater than 0 and is 1 or less. [5] A functional layer with an adhesive layer described in any one of [1] to [4], wherein the functional layer comprises a polymer layer having a glass transition temperature and softening point temperature of 0°C or higher and a thickness in the range of 1 μm to 1 mm. [6] The functional layer with an adhesive layer according to [5], wherein the polymer layer has at least one property selected from the group consisting of polarizing properties, specific wavelength absorption properties, light control properties, and color control properties. [7] The functional layer with an adhesive layer described in any one of [1] to [6], wherein the thickness of the curable adhesive layer AD2 is less than 100 μm. [8] A functional layer with an adhesive layer described in any one of [1] to [7], wherein the curable adhesive layer AD2 contains at least one curable polymer selected from the group consisting of esters, epoxies, urethanes, and (meth)acrylics, and a curing accelerator. [9] The functional layer with an adhesive layer according to any one of [1] to [8], wherein the curable adhesive layer AD2 further satisfies the following requirements: (5) The refractive index (JIS K7142) after curing is 1.45 or more.

[10] The functional layer with an adhesive layer described in [5] or [6], wherein the polymer layer is a substantially uniaxially stretched film.

[11] The functional layer with an adhesive layer according to

[10] , wherein the polymer layer is a polarizing film containing polyethylene terephthalate.

[12] with a functional layer; with adhesive layer AD2-1; A substrate; In this order, A substrate with a functional layer, wherein an adhesive layer AD2-1 is disposed in at least a portion between the opposing surfaces of the functional layer and the substrate, and the adhesive layer satisfies the following requirement (i): (i) The ratio of the amount of plastic deformation b to the amount of elastic deformation a at 25°C and a load of 0.1 mN (b / a) is 0.01 to 100.

[13] The substrate with a functional layer according to

[12] , wherein the adhesive layer AD2-1 satisfies the following requirement (ii): (ii) Dynamic hardness (DHT115-2) after unloading a 0.1 mN load at 25°C is 0.01 to 5000

[14] The substrate with a functional layer according to

[12] or

[13] , wherein the adhesive layer AD2-1 satisfies the following requirement (iii): (iii) A storage modulus at 25°C of 0.5 MPa or more and 1000 MPa or less

[15] A protective layer; Functional layer and; with adhesive layer AD2-1; A substrate; In this order, A laminate, wherein the adhesive layer AD2-1 is disposed in at least a portion between the opposing surfaces of the functional layer and the substrate, and wherein the protective layer satisfies all of the following requirements (a), (b) and (c), and the adhesive layer AD2-1 satisfies the following requirement (i). (a) Thickness: 10μm~1mm (b) At 25°C, the ratio of the amount of plastic deformation b to the amount of elastic deformation a under a load of 0.1 mN (b / a) is 0.1 to 10 (c) At 25°C, the dynamic hardness (DHT115-2) after unloading a 0.1 mN load is 400 to 3000 (i) A storage modulus at 25°C of 0.5 MPa or more and 1000 MPa or less

[16] The laminate according to

[15] , wherein the protective layer satisfies the following requirement (d): (d) Pencil hardness: HB~9H

[17] Further, an adhesive layer AD1-1 is provided between the protective layer and the functional layer, The laminate according to

[15] or

[16] , wherein the adhesive layer AD1-1 satisfies the following requirement (i): (i) The ratio of the amount of plastic deformation b to the amount of elastic deformation a at 25°C and a load of 0.1 mN (b / a) is 0.01 to 100.

[18] The laminate according to

[17] , wherein the adhesive layer AD1-1 satisfies the following requirement (ii): (ii) Dynamic hardness (DHT115-2) after unloading a 0.1 mN load at 25°C is 0.01 to 5000

[19] The laminate according to

[17] or

[18] , wherein the adhesive layer AD1-1 satisfies the following requirement (iii): (iii) A storage modulus at 25°C of 0.5 MPa or more and 1000 MPa or less

[20] An optical component comprising a substrate with a functional layer according to any one of

[12] to

[14] or a laminate according to any one of

[15] to

[19] , wherein the substrate is a lens having a refractive index of 1.49 or more.

[21] The optical component according to

[20] , wherein the adhesive layer AD2-1 contacts at least a portion of the surface of the lens.

[22] The optical component according to

[20] or

[21] , wherein the lens contains one or more materials selected from the group consisting of polycarbonate resin, polyester resin, polyester copolymer, polyamide resin, polyimide resin, poly(meth)acrylate resin, polyolefin resin, polyureaurethane resin, poly(thio)urethane resin, polysulfide resin, poly(meth)(thio)acrylate resin, allyl diglycidyl carbonate resin, and inorganic glass.

[23] The optical component described in

[22] , wherein the functional layer is a polarizing lens having polarizing properties. In this specification, for example, 1 to 10 means 1 or more and 10 or less. Effect of the Invention

[0013] According to the present invention, it is possible to provide a functional layer with an adhesive layer that is excellent in adhesion between the functional layer and a substrate, and further in adhesion at the outer peripheral edge during annealing. Further, according to the present invention, machineIt is also possible to provide a laminate that has excellent adhesion between the functional layer and the substrate, and further excellent adhesion at the outer peripheral edge during annealing, and that suppresses the occurrence of processing residues at the outer peripheral edge during processing of the periphery of the lens. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The functional layer with an adhesive layer, the substrate with a functional layer, and the laminate of the present invention will be described based on embodiments. <Functional layer with adhesive layer> The functional layer with an adhesive layer (functional film with an adhesive layer) of this embodiment includes a functional layer and a curable adhesive layer AD2 disposed on at least a portion of the surface of the functional layer.

[0015] [Functional layer] The functional layer is not particularly limited as long as it can be attached to the substrate described below, and layers made of various resins can be used; however, it preferably comprises a polymer layer having a glass transition temperature and softening point of 0°C or higher, more preferably 0°C or higher and 200°C or lower, and particularly preferably 0°C or higher and 180°C or lower, and a thickness in the range of 1 μm to 1 mm, preferably 10 μm to 300 μm, and more preferably 20 μm to 200 μm. When the composition has both a glass transition temperature and a softening point, both of them are in the above-mentioned temperature range, and when the composition has either a glass transition temperature or a softening point, the temperature that the composition has is in the above-mentioned temperature range. In this embodiment, when the composition has multiple glass transition temperatures, the lowest temperature is regarded as the glass transition temperature. In the case of a functional layer including such a polymer layer, the adhesion to the substrate is improved by using the curable adhesive layer AD2.

[0016] The functional layer may be composed of only a polymer layer, or may have a laminate structure in which at least one other layer is laminated on the polymer layer. The polymer layer may be laminated with different layers. The functional layer generally comprises a polymer layer having at least one property selected from the group consisting of polarizing properties, specific wavelength absorption properties, light control properties, and color control properties, but is not necessarily limited to these functions. In order to impart polarization properties, the polymer layer constituting the functional layer can be formed from a polarizing film. As the polarizing film, a film stretched substantially in one axial direction can be used. In this embodiment, it is possible to solve the adhesion problem that occurs particularly when a stretched film having residual stress is used for the functional layer.

[0017] The polarizing film can be made of a thermoplastic resin. Examples of the thermoplastic resin include a single layer or a laminate of multiple layers of thermoplastic polyester, thermoplastic polycarbonate, thermoplastic polyolefin, thermoplastic polyimide, thermoplastic polyamide, polyvinyl alcohol (PVA), triacetyl cellulose (TAC), etc. From the viewpoints of water resistance, heat resistance, and moldability, thermoplastic polyester and thermoplastic polycarbonate are preferred, and from the viewpoints of water resistance and weather resistance, thermoplastic polyester is more preferred.

[0018] Examples of the thermoplastic polyester include polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, with polyethylene terephthalate being preferred from the viewpoints of water resistance, heat resistance, and moldability.

[0019] In order to impart polarization properties, a dichroic dye or the like can be added to the functional layer made of the thermoplastic resin. As the dichroic dye, a known dye is used. For example, it is disclosed in JP-A-61-087757, JP-A-61-285259, JP-A-62-270664, JP-A-62-275163, JP-A-1-103667, etc. Specific examples include anthraquinone-based, quinophthalone-based, azo-based, and other dyes.

[0020] In order to impart specific wavelength absorption, specific dyes or ultraviolet absorbents can be added to the functional layer made of the thermoplastic resin. Representative dyes include anthraquinone dyes, perinone dyes, monoazo dyes, diazo dyes, phthalocyanine dyes, porphyrin dyes, tetraazapon dyes, and the like. RPhthalyl metal complexes, phthalocyanine compounds, squarylium compounds, poly R Examples of the ultraviolet absorbing agent include phyrin metal complexes, naphthalocyanine dyes, merocyanine dyes, methine dyes, etc. Examples of the ultraviolet absorbing agent include benzophenone compounds, triazine compounds, benzotriazole compounds, indole compounds, etc., and these can be used alone or in combination of two or more.

[0021] In order to impart dimming properties, a dimming dye or a dimming pigment can be added to the functional layer made of the thermoplastic resin. As representative dimming dyes or dimming pigments, for example, one or more of spiropyran compounds, spirooxazine compounds, fulgide compounds, naphthopyran compounds, and bisimidazole compounds can be used according to the desired coloring.

[0022] For the purpose of imparting color-tuning properties, known dyes and the like can be added to the functional layer made of the thermoplastic resin.

[0023] When the functional layer has a laminated structure in which at least one other layer is laminated on a polymer layer, various resin layers can be used as the other layer within the scope of not impairing the effects of the present invention. The resin constituting the other layer is a resin different from that of the polymer layer, and examples thereof include a thermoplastic polycarbonate layer, a thermoplastic polyimide layer, a thermoplastic polyamide layer, and a triacetyl cellulose (TAC) layer. By forming the functional layer into a laminated structure, the strength is improved and the moldability and workability can be improved. The overall thickness of the functional layer, which is a laminated structure, is about 20 μm to 3 mm.

[0024] [Curable adhesive layer AD2] The curable adhesive layer AD2 satisfies the following requirement (1). (1) At 25°C, the adhesive layer AD2 is placed on a horizontally adjusted glass plate (platen) without shifting, a 32 g steel ball is placed on top of it, and after holding for 10 seconds, the glass plate is gradually tilted. The upper limit of the angle at which the steel ball begins to roll is 5 degrees or less, preferably 3 degrees or less, and more preferably 2 degrees or less, and the lower limit is preferably 0.01 degrees or more.

[0025] By satisfying the above requirement (1), it is possible to provide a functional layer with an adhesive layer that is less susceptible to adhesion of dirt and other foreign matter to the adhesive layer of the functional layer with an adhesive layer, and that is easier to attach uniformly to the substrate, thereby providing excellent adhesion between the functional layer and the substrate, particularly at locations with a small radius of curvature, and further having excellent adhesion between the functional layer and the substrate at the outer peripheral edge during annealing.

[0026] From the viewpoint of the effects of the present invention, it is preferable that the following requirement (2) is further satisfied. (2) After curing at 90°C for 2 hours, the ratio (b / a) of the plastic deformation b to the elastic deformation a at 25°C under a load of 0.1 mN has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 1 or more, and most preferably 1.5 or more, and an upper limit of 100 or less, preferably 50 or less, more preferably 10 or less, and particularly preferably 5 or less. It is presumed that by having the ratio of the plastic deformation amount b to the elastic deformation amount a within the above range, the force applied to the functional layer by its elasticity when processing the outer peripheral end portion of the functional layer with an adhesive layer can be transmitted while undergoing an appropriate degree of plastic deformation, making it easier to separate the adhesive layer (leaving less residual processing), and / or maintaining the adhesion between the functional layer and the adhesive layer.

[0027] The lower limit of the plastic deformation amount b exceeds 0, preferably is 0.01 or more, more preferably exceeds 0.05, and particularly preferably is 0.1 or more, and the upper limit is 1 or less, preferably is 0.9 or less, more preferably is 0.8 or less, and particularly preferably is 0.6 or less. By having the amount of plastic deformation b within the above range, deformation due to forces applied to the curable adhesive layer, particularly during transportation or processing, such as chuck marks when transported using a chuck, tends to be reduced.

[0028] The amount of elastic deformation and the amount of plastic deformation can be measured under the following conditions. Measuring instrument: Dynamic ultra-micro hardness tester DUH-W201S (manufactured by Shimadzu Corporation) Indenter: Diamond triangular pyramid indenter (edge ​​angle 115°) Temperature: 25℃ Humidity: 50% Maximum load: 0.1mN Depth 1: Maximum indentation depth (μm) when a load of up to the set load (0.1 mN) is applied Depth 2: Indentation depth after unloading (μm) (amount of plastic deformation) Depth 1 - Depth 2 (μm) (Elastic deformation amount)

[0029] By satisfying both of these requirements (1) and (2), it is possible to provide a functional layer with an adhesive layer that has even better adhesion between the functional layer and the substrate, particularly at points with a small radius of curvature, and that has even better adhesion between the functional layer and the substrate at the outer peripheral edge during annealing.

[0030] From the viewpoint of the effects of the present invention, it is preferable that the following requirement (3) is further satisfied. (3) After curing at 90°C for 2 hours, the dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25°C has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 0.5 or more, and particularly preferably 1 or more, and an upper limit of 5000 or less, preferably 3000 or less, more preferably 1000 or less, even more preferably 500 or less, and particularly preferably 250 or less. In addition, after curing at 90°C for 2 hours, the dynamic hardness (DHT115-1) when a load of 0.1 mN is applied at 25°C is preferably 0.1 to 100, and more preferably 0.5 to 50.

[0031] The dynamic hardness can be measured under the following conditions. Measuring instrument: Dynamic ultra-micro hardness tester DUH-W201S (manufactured by Shimadzu Corporation) Indenter: Diamond triangular pyramid indenter (edge ​​angle 115°) Maximum load: 0.1mN Depth 1: Maximum pressing amount when a load of set load (0.1 mN) is applied Depth 2: Indentation depth after unloading (amount of plastic deformation) Depth 1 - Depth 2 (elastic deformation) Dynamic hardness (DHT115-2): Determined by depth 2 and maximum load (0.1 mN). Also, dynamic hardness (DHT115-1): is determined by depth 1 and maximum load (0.1 mN).

[0032] The principle of measuring the dynamic hardness is as follows. Dynamic hardness (dynamic ultra-microhardness) DHT115-1 is the hardness found from the indentation depth when a test load is applied, and is calculated using the following formula. Dynamic hardness DHT115-2 is the hardness calculated in a similar manner from the indentation depth after the load is removed. Note that the calculation results include an error due to deviation from the ideal shape of the indenter. Formula: DHT115=3.8584·P / D 2 DHT115: Dynamic hardness measured with a triangular pyramid indenter with a ridge angle of 115° P: Test load (mN) D: Indentation depth (μm)

[0033] After curing at 90°C for 2 hours, the indentation modulus during the unloading process of a 0.1 mN load measured with the above-mentioned ultra-microhardness tester at 25°C was 10 8 ~10 10 It is also preferred that Pa. The indentation elastic modulus (elastic modulus Y) is a value evaluated from the degree of initial elastic recovery during the unloading process, and is calculated using the formula listed below. Note that the calculation result includes an error due to deviation from the ideal shape of the indenter.

[0034] TIFF0007630994000001.tif78153

[0035] The symbols in the formula are as follows. Y: Elastic modulus of the sample including Poisson's ratio (Pa) E: Elastic modulus of the sample (Pa) E i : Elastic modulus of diamond indenter (1.14×10 12 Pa) E r : Combined elastic modulus of the sample and indenter (Pa) v: Poisson's ratio of the sample v i : Poisson's ratio of diamond indenter (0.07) A: Indentation projected area (m 2 ) dP / dh: Gradient at the start of unloading in the load-indentation depth diagram (N / m) h c : Effective contact depth (m) h max : Maximum pressing depth (m) (depth 1) h r : Intersection of the tangent line at the start of unloading with the depth axis (m) (depth 3) h max -h r :(depth 1)-(depth 3) ...(depth 4)

[0036] From the viewpoint of the effects of the present invention, it is preferable that the following requirement (4) is further satisfied. (4) The storage modulus at 25°C after curing at 90°C for 2 hours is under The limit is 0.5 MPa or more, preferably 1 MPa or more, and more preferably 10 MPa or more, and the upper limit is 1000 MPa or less, preferably 800 MPa or less, and more preferably 600 MPa or less.

[0037] By satisfying these requirements (3) and / or (4), it is possible to provide a functional layer with an adhesive layer that has particularly excellent adhesion between the functional layer and the substrate, particularly at locations with a small radius of curvature, and further has particularly excellent adhesion between the functional layer and the substrate at the outer peripheral edge during annealing.

[0038] The curable adhesive layer AD2 can have an adhesive strength (JIS Z1528; to glass) after curing at 90° C. for 2 hours of 5 N / 25 mm or more, preferably 10 N / 25 mm or more, and more preferably 15 N / 25 mm or more. If the curable adhesive layer AD2 has the above adhesive strength, sufficient adhesive strength can be ensured even when it is attached to a substrate or the like.

[0039] The curable adhesive layer AD2 preferably further satisfies the following requirement (5). Alternatively, the difference in refractive index from the substrate is preferably 0.1 or less, more preferably 0.05 or less. This ensures excellent optical properties even when the functional layer with the adhesive layer is used for optical purposes. In particular, birefringence when laminated with the substrate can be suppressed. (5) The refractive index (JIS K7142) after curing at 90° C. for 2 hours is 1.45 or more, preferably 1.50 or more, and more preferably 1.60 or more.

[0040] The thickness of the curable adhesive layer AD2 can be less than 100 μm, preferably 80 μm or less, and more preferably 50 μm or less. In this embodiment, the curable adhesive layer AD2 is provided, and the lower limit of the thickness is not particularly limited, but is 5 μm or more, preferably 10 μm or more, and more preferably 20 μm or more. When the thickness of the curable adhesive layer AD2 is within this range, the adhesiveness to the functional layer or the substrate is excellent, and the adhesion between the functional layer and the substrate can be further improved.

[0041] The curable adhesive layer AD2 contains at least one type of curable polymer selected from the group consisting of ester-based, epoxy-based, urethane-based, and acrylic-based polymers, and a curing accelerator.

[0042] Examples of the ester-based resin include ester-based, polyester-based, polyester-urethane-based, and (meth)acrylic-polyester-based resins. Examples of the epoxy resin include epoxy, (meth)acrylic-epoxy, epoxy-urethane, and epoxy-polyester resins. Examples of the urethane-based resin include urethane-based, urethane-(meth)acrylic, and urethane-ester-based resins. Examples of the (meth)acrylic resin include (meth)acrylic, (meth)acrylic-urethane, acrylic-epoxy, acrylic-polyester, etc. Note that (meth)acrylic includes both methacrylate and acrylate. Curing accelerators include amines and gold. genus confusion Examples of such systems include: The curable adhesive layer AD2 may contain other components such as antioxidants, light stabilizers, deterioration inhibitors, and UV absorbers in addition to the above-mentioned resins.

[0043] It is preferable that the curable adhesive layer AD2 does not contain any component having a boiling point of 100° C. or less, which can prevent contamination of the lens in the step of attaching it to the lens (thermocompression bonding).

[0044] The functional layer with an adhesive layer of this embodiment can be obtained by applying a curable adhesive to at least a part of the surface of the functional film. Examples of the application method include known methods such as spin coating, dip coating, die coating, gravure coating, spray coating, and curtain (flow) coating. Alternatively, it can be obtained by pressing a sheet-shaped curable adhesive layer onto at least a part of the surface of the functional film, or by heat lamination. The curable adhesive layer AD2 is disposed on at least a portion of a surface of the functional layer, preferably on at least a portion of one surface of the functional layer.

[0045] <Substrate with functional layer> The substrate with a functional layer of this embodiment includes a functional layer, an adhesive layer AD2-1, and a substrate in this order. The substrate with a functional layer of this embodiment uses the above-mentioned functional layer with an adhesive layer, and therefore has excellent adhesion between the functional layer and the substrate, particularly in areas with a small radius of curvature, and further has excellent adhesion at the outer peripheral edge during annealing.

[0046] [Functional layer] The functional layer in this embodiment may be the same as that described above in the functional layer with an adhesive layer.

[0047] [Adhesive layer AD2-1] The adhesive layer AD2-1 is disposed at least partially between the two opposing surfaces of the functional layer and the substrate, and from the viewpoint of the effects of the present invention, it is preferable that the adhesive layer AD2-1 satisfies the following requirement (i). (i) The ratio (b / a) of the plastic deformation b to the elastic deformation a at 25°C and a load of 0.1 mN has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 1 or more, and most preferably 1.5 or more, and an upper limit of 100 or less, preferably 50 or less, more preferably 10 or less, and particularly preferably 5 or less. It is presumed that by having the ratio of the plastic deformation amount b to the elastic deformation amount a within the above range, the force applied to the functional layer by elasticity when processing the outer peripheral end portion of the functional layer with an adhesive layer can be transmitted while undergoing an appropriate degree of plastic deformation, making it easier to separate the adhesive layer (leaving less residual processing), and / or maintaining the adhesion between the functional layer and the adhesive layer.

[0048] The lower limit of the plastic deformation amount b exceeds 0, preferably is 0.01 or more, more preferably exceeds 0.05, and particularly preferably is 0.1 or more, and the upper limit is 1 or less, preferably is 0.9 or less, more preferably is 0.8 or less, and particularly preferably is 0.6 or less. By having the amount of plastic deformation b within the above range, deformation due to forces applied to the curable adhesive layer, particularly during transportation or processing, such as chuck marks when transported using a chuck, tends to be reduced.

[0049] It is preferable that the adhesive layer AD2-1 further satisfies the following requirement (ii). (ii) The dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25°C has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 0.5 or more, and particularly preferably 1 or more, and an upper limit of 5000 or less, preferably 3000 or less, more preferably 1000 or less, even more preferably 500 or less, and particularly preferably 250 or less.

[0050] It is also preferable that the dynamic hardness (DHT115-1) is 1 to 100 when a load of 0.1 mN is applied at 25°C. In addition, the indentation elastic modulus during the unloading process of a 0.1 mN load measured with the above-mentioned ultra-microhardness tester at 25°C is 10 8 ~10 10 It is also preferred that Pa.

[0051] It is also preferable that the adhesive layer AD2-1 further satisfies the following requirement (iii). (iii) The storage modulus at 25° C. has a lower limit of 0.5 MPa or more, preferably 1 MPa or more, and more preferably 10 MPa or more, and an upper limit of 1000 MPa or less, preferably 800 MPa or less, and more preferably 600 MPa or less.

[0052] The thickness of the adhesive layer AD2-1 is substantially the same as that of the curable adhesive layer AD2, and can be less than 100 μm, preferably 80 μm or less, and more preferably 50 μm or less. In this embodiment, it is sufficient that the adhesive layer AD2-1 is provided, and the lower limit of the thickness is not particularly limited, but is 5 μm or more, preferably 10 μm or more, and more preferably 20 μm or more.

[0053] The adhesive layer AD2-1 can be obtained by curing the curable adhesive layer AD2. The curing method can be heat curing or curing by irradiation with energy rays such as ultraviolet rays or visible light. Law etc. For example, as described below, the curable adhesive layer AD2 is brought into contact with the surface of the substrate and then cured to form an adhesive layer AD2-1, and the substrate and the functional layer can be bonded together via the adhesive layer AD2-1.

[0054] [Base material] The substrate may be a thermoplastic resin or a thermosetting resin, and the shape is not limited to a lens shape, etc. Examples of the thermoplastic resin include polycarbonate resin, polyester resin, polyester copolymer, polyamide (nylon) resin, polyimide resin, poly(meth)acrylate resin, polyolefin resin, etc., and polycarbonate resin, polyester resin, polyamide (nylon) resin, etc. are preferred. Examples of the thermosetting resin include polyurea urethane resin, poly(thio)urethane resin, polysulfide resin, poly(meth)(thio)acrylate resin, and allyl diglycidyl carbonate (ADC) resin. The thermosetting resin can be obtained by curing and molding a polymerizable composition containing a polymerization reactive compound by a predetermined method. Examples of the polymerization reactive compound contained in the polymerizable composition include a polyisocyanate compound and a poly(thio)ol compound. The substrate may be inorganic (optical) glass. These materials are highly transparent and can be suitably used as a resin substrate for optical materials. These materials may be used alone or in combination.

[0055] The polyisocyanate compound can be selected from conventionally known compounds as long as it can obtain the effects of the present invention, and examples of the polyisocyanate compound include the compounds exemplified in WO2011 / 055540.

[0056] Specific examples of polyisocyanate compounds include xylylene diisocyanate, phenylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, 2,5-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, 2,6-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, bis(isocyanatocyclohexyl)methane, hexamethylene diisocyanate, pentamethylene diisocyanate, and isophorone isocyanate, and at least one selected from these can be used.

[0057] Of the poly(thio)ol compounds, the polyol compound can be selected from conventionally known compounds as long as the effects of the present invention can be obtained. For example, the compounds disclosed in WO2017 / 47725 can be used.

[0058] The polythiol compound can be selected from conventionally known compounds as long as it can obtain the effects of the present invention. For example, the compounds disclosed in WO2008 / 105138 can be used. Specific examples of the polythiol compound include pentaerythritol tetrakis(2-mercaptoacetate), pentaerythritol tetrakis(3-mercaptopropionate), bis(mercaptoethyl)sulfide, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4, Examples of the monomer include 8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 2,5-dimercaptomethyl-1,4-dithiane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithietane, and ethylene glycol bis(3-mercaptopropionate). At least one selected from these monomers can be used.

[0059] The substrate with a functional layer of this embodiment uses a functional layer with an adhesive layer and has a small radius of curvature. Basic The adhesion between the functional layer and the substrate is excellent even on the substrate surface, and also on the substrate surface with a lens front curve of 6C or more. Basic The material surface is merely an example, and the adhesive has excellent adhesion to uneven substrate surfaces. The thickness of the substrate is about 1 to 20 mm.

[0060] [Method of manufacturing substrate with functional layer] The substrate with a functional layer in this embodiment can be prepared, although not particularly limited, by laminating a curable adhesive layer AD2 of a functional layer with an adhesive layer on one side of the substrate, and curing the curable adhesive layer AD2 by thermal curing or exposure to energy rays such as ultraviolet light or visible light to form an adhesive layer AD2-1.

[0061] Thereafter, the substrate with the functional layer may be subjected to a treatment such as annealing. The treatment is usually performed at a temperature between 50 and 150°C, preferably between 90 and 140°C, and more preferably between 90 and 130°C. The substrate with the functional layer of this embodiment uses a functional layer with an adhesive layer, and has excellent adhesion between the functional layer and the substrate even during annealing. In addition, a hard coat layer, an anti-reflection layer, an anti-fogging layer, an anti-pollution layer, a water-repellent layer, and a light-controlling layer can be formed on the substrate with the functional layer as necessary.

[0062] <Laminate> The laminate of this embodiment comprises, in this order, a protective layer, a functional layer, an adhesive layer AD2-1, and a substrate, and the adhesive layer AD2-1 is disposed at least partially between the two opposing surfaces of the functional layer and the substrate.

[0063] According to the laminate of this embodiment, machine The adhesion between the functional layer and the substrate is excellent, particularly in areas with small radii of curvature, and is also excellent in adhesion at the outer peripheral edge during annealing. This suppresses the generation of machining residues at the outer peripheral edge during peripheral processing of substrates such as lenses, and reduces the amount of shavings. The functional layer, adhesive layer AD2-1, and substrate are the same as those in the above embodiment, and therefore description thereof will be omitted.

[0064] [Protective layer] The protective layer preferably satisfies the following requirements (a), (b) and (c). (a) The lower limit of the thickness is 10 μm or more, preferably 20 μm or more, and more preferably 30 μm or more, and the upper limit is 1 mm or less, preferably 0.8 mm or less, and more preferably 0.5 mm or less. (b) At 25°C, the ratio (b / a) of the plastic deformation b to the elastic deformation a under a load of 0.1 mN has a lower limit of 0.1 or more, preferably 0.5 or more, more preferably 1 or more, and most preferably 1.5 or more, and an upper limit of 10 or less, preferably 5 or less, and more preferably 2 or less. (c) The dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25°C has a lower limit of 400 or more, preferably 500 or more, and more preferably 550 or more, and an upper limit of 3000 or less, preferably 2500 or less, and more preferably 2000 or less. When the protective layer satisfies all of the requirements (a), (b) and (c), the occurrence of unprocessed portions and / or chipping at the outer peripheral edge portion during peripheral processing of the lens is suppressed.

[0065] It is also preferable that the dynamic hardness (DHT115-1) is 70 to 150 when a load of 0.1 mN is applied at 25°C. In addition, the indentation elastic modulus during the unloading process of a 0.1 mN load measured with the above-mentioned ultra-microhardness tester at 25°C is 5×10 9 ~2×10 10 It is also preferred that Pa.

[0066] From the viewpoint of the effects of the present invention, it is preferable that the protective layer further satisfies the following requirement (d). (d) The pencil hardness has a lower limit of HB or more, preferably H or more, and more preferably 2H, and an upper limit of 9H or less, preferably 6H or less.

[0067] The protective layer has a Young's modulus of preferably 0.3 GPa or more, more preferably 0.5 GPa or more, and even more preferably 1 GPa or more, and preferably 10 GPa or less, more preferably 8 GPa or less, and even more preferably 5 GPa or less. When the Young's modulus falls within this range, the protective layer has excellent flexibility and toughness, and therefore the occurrence of processing residues at the outer peripheral edge during processing of the outer periphery of the lens is further suppressed.

[0068] The protective layer is formed by applying a resin composition by a known application method such as spin coating, dip coating, casting, etc., and then curing the composition. The application method is appropriately selected depending on the film thickness and surface shape of the protective layer. For example, when the thickness of the protective layer to be formed is about 300 μm, spin coating, dip coating, etc. are preferred, and when the thickness is greater than that, a casting method is preferred from the viewpoint of the surface shape.

[0069] The protective layer can also be prepared by laminating a resin sheet or film. When the protective layer is formed by laminating a resin sheet or film, it is preferable that the resin sheet or film satisfies the following requirement (e). (e) The lower limit of the flexibility is 0 mm or more, preferably 2 mm or more, and more preferably 3 mm or more, and the upper limit is 100 mm or less, preferably 50 mm or less, and more preferably 40 mm or less. The flexibility means the minimum diameter of a cylinder that can be wrapped around a resin sheet or film without causing breakage or cracking in the resin sheet or film when the resin sheet or film is wrapped around the cylinder of a certain diameter. When the resin sheet or film constituting the protective layer satisfies the requirement (e), the occurrence of processing insufficiencies at the outer peripheral edge during processing of the outer periphery of the lens is further suppressed.

[0070] Examples of the curable resin contained in the protective layer include optical materials such as epoxy-based, urethane acrylate-based, epoxy acrylate-based, urethane-based, acrylic-based, and thiourethane-based materials, and at least one selected from these can be used.

[0071] The protective layer can be formed by applying a resin composition by a known application method such as spin coating, dip coating, spray coating, curtain coating, etc., and then curing the applied layer. It can also be formed by a casting method. In the case of forming the protective layer by a casting method, it is preferable that the protective layer contains (thio)urethane, urethane urea, (meth)acrylic, epoxy, urethane (meth)acrylate, episulfide, and allyl diglycidyl carbonate. The laminate of this embodiment can be obtained by forming a protective layer on the functional layer of the substrate with the functional layer. Examples of the curing method include a curing method using heat curing and irradiation with energy rays such as ultraviolet rays and visible light. In order to suppress the occurrence of interference fringes, the refractive index of the protective layer is preferably different from that of the lens in the range of ±0.1.

[0072] In this embodiment, it is preferable to provide an adhesive layer AD1-1 between the protective layer and the functional layer. The adhesive layer AD1-1 preferably satisfies the following requirement (i). (i) The ratio (b / a) of the plastic deformation b to the elastic deformation a at 25°C and a load of 0.1 mN has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 1 or more, and most preferably 1.5 or more, and an upper limit of 100 or less, preferably 50 or less, more preferably 10 or less, and particularly preferably 5 or less. It is presumed that by having the ratio of the plastic deformation amount b to the elastic deformation amount a within the above range, the force applied to the functional layer by elasticity when processing the outer peripheral end portion of the functional layer with an adhesive layer can be transmitted while undergoing an appropriate degree of plastic deformation, making it easier to separate the adhesive layer (leaving less residual processing), and / or maintaining the adhesion between the functional layer and the adhesive layer.

[0073] The lower limit of the plastic deformation amount b exceeds 0, preferably is 0.01 or more, more preferably exceeds 0.05, and particularly preferably is 0.1 or more, and the upper limit is 1 or less, preferably is 0.9 or less, more preferably is 0.8 or less, and particularly preferably is 0.6 or less. By having the amount of plastic deformation b within the above range, deformation due to forces applied to the curable adhesive layer, particularly during transportation or processing, such as chuck marks when transported using a chuck, tends to be reduced.

[0074] It is preferable that the adhesive layer AD1-1 further satisfies the following requirement (ii). (ii) The dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25°C has a lower limit of 0.01 or more, preferably 0.1 or more, more preferably 0.5 or more, and particularly preferably 1 or more, and an upper limit of 5000 or less, preferably 3000 or less, more preferably 1000 or less, even more preferably 500 or less, and particularly preferably 250 or less.

[0075] It is also preferable that the dynamic hardness (DHT115-1) is 1 to 100 when a load of 0.1 mN is applied at 25°C after curing at 90°C for 2 hours. In addition, the indentation elastic modulus during the unloading process of a 0.1 mN load measured with the above-mentioned ultra-microhardness tester at 25°C is 10 8 ~10 10 It is also preferred that Pa.

[0076] It is also preferable that the adhesive layer AD1-1 further satisfies the following requirement (iii). (iii) The storage modulus at 25° C. has a lower limit of 0.5 MPa or more, preferably 1 MPa or more, and more preferably 10 MPa or more, and an upper limit of 1000 MPa or less, preferably 800 MPa or less, and more preferably 500 MPa or less. The adhesive layer AD1-1 can be obtained by curing the curable adhesive layer AD1, and the curable adhesive layer AD2 can be used as the curable adhesive layer AD1. The curable adhesive layer AD2 may be the same as or different from the curable adhesive layer AD1.

[0077] In this embodiment, a curable adhesive layer AD1 is provided on the functional layer of the functional layer with an adhesive layer (curable adhesive layer AD2 / functional layer), and the curable adhesive layer AD2 is bonded to a substrate and then cured to form an adhesive layer AD1-1 together with the adhesive layer AD2-1 (substrate with functional layer). Alternatively, the curable adhesive layer AD2 of the functional layer with an adhesive layer (curable adhesive layer AD2 / functional layer) can be bonded to a substrate, and a curable adhesive layer AD1 is provided on the functional layer and then cured to form an adhesive layer AD1-1 together with the adhesive layer AD2-1 (substrate with functional layer).

[0078] A protective layer can be formed (laminate) by a method of applying the resin composition onto the adhesive layer AD1-1 of a substrate with a functional layer and curing it, by laminating the resin composition onto the adhesive layer AD1-1 by a casting method and curing it, or by a method of laminating the resin sheet or the like onto the adhesive layer AD1-1.

[0079] This improves the adhesion between the protective layer and the functional layer, further suppresses the generation of machining residues at the outer peripheral edge during peripheral processing of the lens, and further reduces the amount of shavings. On the protective layer, a hard coat layer, an anti-reflection layer, an anti-fogging layer, an anti-pollution layer, a water-repellent layer, and a light-adjusting layer may be formed as necessary.

[0080] <Optical components> The optical component of this embodiment can be constructed from the above-mentioned functional layer-attached substrate or laminate, and the adhesive layer AD2-1 can be in contact with at least a part of the surface of the lens. The substrate is preferably a lens having a refractive index of 1.49 or more.

[0081] Examples of optical components include polarized lenses in which the functional layer has polarizing properties, blue light cut lenses in which the functional layer has specific wavelength absorption properties, specific wavelength cut lenses (Neocontrast (R) (585 nm cut)), and photochromic lenses in which the functional layer has photochromic properties. Generally, the lens (substrate) surface on which the functional layer is laminated is the objective surface, and the back surface is the eye surface.

[0082] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0084] In the present examples, the physical properties were measured by the following methods. <Tackiness> At 25°C, two flat glass plates, 580 mm square and 10 mm thick, were used, one of which was used as a base plate, the other was placed on top of which, and a 5 cm square curable adhesive layer AD2 was placed on top of the base plate. A 32 g steel ball was placed on the curable adhesive layer AD2, and after holding for 10 seconds, one end of the upper glass plate was gradually raised, and the angle DEG at which the steel ball rolled down from the curable adhesive layer AD2 was measured (the angle was calculated by the inverse trigonometric function ARC SIN (height / hypotenuse) with the length of the rise (height) and the length of the glass plate (hypotenuse) when one side was raised), and was evaluated as tackiness. The rolling angle when a 32 g steel ball was placed on the glass plate was 0.49 degrees.

[0085] <Storage modulus> The storage modulus of the adhesive layer after curing was measured at a frequency of 1 Hz and 25°C using a storage modulus measuring device (DVA (manufactured by IT Measurement Co., Ltd.), RSA-3 (manufactured by TI Instruments), DMA-6100 (manufactured by Seiko Instruments Co., Ltd.) and a measuring device (Physica MCR301) manufactured by Anton Paar.

[0086] <Parallel light transmittance (unit: %)> The total light transmittance of the adhesive layer with a thickness of 2 mm was measured using a Haze Meter (manufactured by Nippon Denshoku Industries Co., Ltd., model: NDH 2000). If the adhesive layer has anisotropy in the MD or TD direction, the total light transmittance was measured in the TD and MD directions, and the average value was taken as the total light transmittance of the adhesive layer. <Pencil hardness test> The pencil hardness test specified in ISO15 184 was carried out to confirm the pencil hardness of the protective layer.

[0087] <Flexibility> Cylinders with diameters of 1 mm to 100 mm were prepared at 1 mm intervals, and when the membrane or film was pressed against the cylinders and wrapped around them, the minimum diameter of the cylinder that could be wrapped without causing breaks or cracks in the membrane or film was defined as the bending strength. A bending strength of 0 mm means that the film will not break when bent. <Young's modulus> Young's modulus (flexural modulus) was measured at one point each in the MD and TD directions with reference to the bending strength test described in JIS A5905, under conditions of 23°C and 50% RH, specimen thickness: 3 mm, specimen width: 50 mm, specimen length: 150 mm, span distance: 100 mm, and bending speed: 50 mm / min, and the average value was used.

[0088] <Microhardness test> Measuring instrument: Dynamic ultra-micro hardness tester DUH-W201S (manufactured by Shimadzu Corporation) Indenter: Diamond triangular pyramid indenter (edge ​​angle 115°) Temperature: 25℃ Humidity: 50% Maximum load: 0.1mN Depth 1: Maximum indentation amount (μm) when a load of set load (0.1 mN) is applied (The maximum pressing amount was measured in a place where there was no influence from the lower layers such as the base layer.) Depth 2: Indentation depth after unloading (μm) (amount of plastic deformation) Depth 1 - Depth 2 (μm) (Elastic deformation amount) Dynamic hardness (DHT115-1): Calculate from the following formula using depth 1 and maximum load (0.1 mN). Dynamic hardness (DHT115-2): Determined from depth 2 and maximum load (0.1 mN). Formula: DHT115=3.8584·P / D 2 DHT115: Dynamic hardness measured with a triangular pyramid indenter with a ridge angle of 115° P: Test load (mN) D: Indentation depth (μm) Indentation elastic modulus (Pa): This is a value evaluated from the degree of initial elastic recovery during the unloading process, and is calculated using the above formula.

[0089] <Adhesion at the outer edge (after application, before curing): Corresponds to the adhesion at the outer edge of the high curve lens in the table (when applied at 6C or more)> Under the conditions described in the examples, a functional layer with curable adhesive layer AD2-1 was attached so that the adhesive layer was in contact with the convex surface of a 6C lens, and then after 10 minutes, whether the functional layer had peeled off from the substrate at the outer periphery of the edge of the lens was evaluated using the following criteria. ○: Almost no peeling from the substrate was visible around the entire circumference of the lens, or slight peeling was visible around 1 / 4 or less of the circumference of the lens, but not noticeable (0 to 0.3 mm peeling from the outer circumference toward the center) △: Peeling from the substrate was visually observed at least at some edges of the outer periphery of the lens (peelation from the outer periphery edge toward the center was less than 2 to 3 mm) ×: Peeling from the substrate is clearly visible at least at some edge portions of the outer periphery of the lens (peeling of 3 mm or more from the outer periphery edge toward the center).

[0090] <Adhesion of the outer edge (after hardening, before edging): corresponds to the adhesion of the lens outer edge in the table (during annealing)> The lens obtained by bonding and curing the outer peripheral edge (after bonding, before curing) was annealed at 120°C for 2 hours, and then the adhesion of the functional layer to the substrate was evaluated. The evaluation criteria were the same as those for the outer peripheral edge (after bonding, before curing).

[0091] <Adhesion at the outer edge (when machining into a round shape): Corresponds to the machining residue in Table 2> The adhesion of the functional layer to the substrate when a lens not provided with a protective layer was edged was evaluated. The evaluation criteria were the same as those for the adhesion of the outer peripheral edge. The lens having the protective layer was subjected to edge processing, and the adhesion between the protective layer and the functional layer at the outer periphery of the edge of the lens was evaluated according to the following criteria. ◯: No residual cutting (burrs, residue) or poor appearance (peeling, cracks) was observed. △: No uncut areas were observed, but defects in appearance were observed within a range of 0.3 mm or less from the outer periphery toward the center. ×: Uncut areas were observed, and furthermore, defective appearance was observed in a distance of more than 0.3 mm from the outer periphery toward the center.

[0092] <Chuck marks during machining> After a lens having a functional layer with an adhesive layer attached thereto was subjected to edge processing under the conditions described in the examples, the marks of the chuck that fixed the lens during processing were left as distortions in the adhesive layer, and were evaluated by visually checking whether they remained on the functional layer.

[0093] <Evaluation of remaining processing> When the outer edge was smoothed (ground) using a curve generator (manufactured by Satislow) before grinding the back surface for strength application, the outer edge of the functional layer was evaluated based on whether or not processing residue was generated and the layer was frayed (frayed, also known as "fuzz"). ×: The functional layer is deformed during processing and peels off from the lens, or the maximum length of the processing residue exceeds 1 mm. △: The maximum length of the machining residue is more than 0.5 mm and 1 mm or less 〇: Maximum length of remaining part is 0.5mm or less ◎: No residual processing can be visually confirmed, and the ground surface is smooth. Edger (bevel processing machine: NIDE K When the surface was rubbed with a LEX1000 (Kansai Electric Co., Ltd.), there was no appearance defect (peeling, cracking), no remaining cutting residue (burrs, debris adhesion), and no abnormal stop (probe caught due to burrs or debris adhesion). Regarding debris adhesion, those that could be easily removed by hand were rated as ◯.

[0094] [Example 1] Using a known extrusion film molding method, a dichroic dye, other color-adjusting dyes, functional materials, and other additives were kneaded into dried pellet-shaped polyethylene terephthalate and extruded from a T-die to form a film, which was then uniaxially stretched to obtain a polyethylene terephthalate polarized film [glass transition temperature 70.7°C] (thickness 100 to 140 microns). A polyester-based thermosetting sheet adhesive (Nikaflex(R) SAFS, manufactured by Nikkan Industries, tackiness 0.9 degrees, storage modulus after curing 400MPa) was laminated or directly applied to the surface at 100°C and dried to obtain a functional layer with a curable adhesive layer AD2. Next, 50.6 parts by weight of m-xylylene diisocyanate, 49.4 parts by weight of a mixture of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.01 parts by weight of dibutyltin dichloride as a curing accelerator, 0.1 parts by weight of Zelec UN (registered trademark, manufactured by Stepan Co., Ltd.) as a mold release agent, and 0.05 parts by weight of Seesorb 709 (manufactured by Shipro Kasei Co., Ltd.) as an ultraviolet absorber were stirred and dissolved, and then degassed under reduced pressure, and immediately after preparation, the mixture was used as a monomer mixture for injection. The viscosity at 20°C after 1 hour of stirring and dissolving was 30 mPa·s. This injection monomer mixture (lens material 1) was injected into a lens casting mold, heated from 25°C to 100°C over 16 hours in an oven, then maintained at 100°C for 10 hours, slowly cooled, and the lens casting mold was removed from the oven. The lens was released from the lens casting mold and annealed at 115°C for 2 hours to obtain a semi-finished lens with an outer diameter of 75φ, a radius of curvature of 88mm, and a thickness of 15mm at the center of the lens. The adhesive layer AD2 of the functional layer with the curable adhesive layer AD2 was brought into contact with the convex surface of the lens with a radius of curvature of 88 mm, heated at 160°C, and laminated while stretching it along the convex surface, and cured at 90°C for 2 hours to produce a substrate with a functional layer (hereinafter, when a lens is used as the substrate, it is also called a "lens with a functional layer") that has a functional layer, an adhesive layer AD2-1, and a lens (substrate) in that order. The refractive index (JIS K7142) of the adhesive layer AD2-1 was 1.67. Even after curing at 90°C for 2 hours, there was no peeling or adhesive misalignment on the outer periphery. Furthermore, when the lens with the hardened functional layer was annealed in an oven at 120° C. for 2 hours, no peeling of the outer periphery or adhesion deviation occurred. Next, the outer periphery was ground and adjusted using a curve generator (manufactured by Satislaw) before grinding the back surface, to obtain a lens with an outer diameter of 70φ and a thickness of 2 mm at the lens center. Next, the lenses with the functional layer were edged to a width of 49 mm and a height of 28 mm in dry mode using a Nidek edger (edging machine) (LEX-1000), and the adhesion between the functional layer and the lens (substrate) was evaluated. The evaluation results are shown in Table 1.

[0095] [Example 2] The procedure of Example 1 was followed, but the material was changed to a commercially available lens material RAV 7AT (diallyl 2,2'-oxydiethyl dicarbonate, manufactured by ACOMON), and a RAV 7AT substrate (lens) having a diameter of 75φ, a thickness at the center of the lens of 2 mm, and a radius of curvature of 88 mm was prepared according to a known preparation method. The adhesive layer was cured at 90° C. for 2 hours in the same manner as in Example 1, but no peeling or displacement of the functional layer was observed. Furthermore, no peeling or displacement was observed even after annealing at 120° C. for 2 hours. Next, the lenses with the functional layer were edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm, and the adhesion between the functional layer and the lens (substrate) was evaluated. There was no peeling between the functional layer and the substrate, and no processing residue was found on the functional layer, resulting in a good result. The evaluation results are shown in Table 1.

[0096] [Example 3] In 31.8 parts by mass of bis(2,3-epithiopropyl)disulfide, 0.007 parts by mass of N,N-dimethylcyclohexylamine and 0.032 parts by mass of N,N-dicyclohexylmethylamine were dissolved, and 3.2 parts by mass of a mixture mainly composed of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane was added and stirred for 30 minutes at 20° C. to prepare a prepared liquid. This prepared liquid was degassed for 1 hour at 600 Pa, filtered with a 1 μm PTFE filter, and then poured into a planar glass mold with a center thickness of 2 mm and a diameter of 80 mm. The temperature of this glass mold was gradually raised from 30°C over 19 hours to 80°C, and then kept at 80°C for 2 hours. It was cooled to room temperature and removed from the glass mold to obtain a lens. The obtained lens was further annealed at 120°C for 3 hours to obtain a semi-finished lens shape (refractive index 1.74) with an outer diameter of 75φ, a radius of curvature of 88 mm, and a thickness of 2 mm at the lens center. As in Example 1, the functional layer with an adhesive layer was stretched and bonded to the substrate, and cured at 90°C for 2 hours to obtain a lens with a functional layer having, in that order, a functional layer with a refractive index of 1.74, an adhesive layer AD2-1, and a lens (substrate). The curable adhesive layer AD2 was cured at 90° C. for 2 hours, but no peeling or misalignment of the functional layer was observed. Also, no peeling or misalignment was observed after annealing at 120° C. for 2 hours. Next, the lens with the functional layer was edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and there was no residual processing of the functional layer, resulting in good results. The evaluation results are shown in Table 1.

[0097] [Example 4] The procedure of Example 1 was followed except that the material was changed to lens material 2 (2,5-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, 2,6-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, pentaerythritol tetrakis(3-mercaptopropionate)), and a substrate (lens) having a diameter of 75φ, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was prepared according to a known preparation method. Upilex (polyimide film, manufactured by Ube Industries, film thickness 50 microns) was used for the functional layer, and a functional layer with an adhesive layer was obtained in the same manner as in Example 1. The functional layer was then stretched and attached to the substrate of lens material 2, and cured at 90°C for 2 hours to obtain a lens with a functional layer. The curable adhesive layer AD2 was cured at 90° C. for 2 hours in the same manner as in Example 1, but no peeling or displacement of the functional layer was observed. Furthermore, no peeling or displacement was observed even after annealing at 120° C. for 2 hours. Next, the lens with the functional layer was edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and there was no residual processing of the functional layer, resulting in good results. The evaluation results are shown in Table 1.

[0098] [Example 5] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. A commercially available TAC / PVA / TAC (manufactured by Sumitomo Bakelite Co., Ltd., total thickness 200 microns (PVA layer: 100 μm, TAC layers on both sides: 50 μm)) was used for the functional layer, and a functional layer with an adhesive layer was obtained using the same method as in Example 1. The functional layer was then stretched and attached to the substrate of lens material 2, and cured at 90°C for 2 hours to obtain a lens with a functional layer. The curable adhesive layer AD2 was cured at 90° C. for 2 hours in the same manner as in Example 1, but no peeling or displacement of the functional layer was observed. Furthermore, no peeling or displacement was observed even after annealing at 120° C. for 2 hours. Next, the lens with the functional layer was edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and no residual processing of the functional layer, and the results were good. The evaluation results are shown in Table 1.

[0099] [Example 6] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. A commercially available PC / PVA / PC (manufactured by Sumitomo Bakelite Co., Ltd., total thickness 700 microns (PVA layer: 60 μm, PC layers on both sides: 320 μm)) was used for the functional layer, and a functional layer with an adhesive layer was obtained in the same manner as in Example 1. The functional layer was then stretched and attached to the substrate of lens material 2 and cured at 90°C for 2 hours to obtain a lens with a functional layer. The curable adhesive layer AD2 was cured at 90° C. for 2 hours in the same manner as in Example 1, but no peeling or displacement of the functional layer was observed. Furthermore, no peeling or displacement was observed even after annealing at 120° C. for 2 hours. Next, the lens with the functional layer was edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and there was no residual processing of the functional layer, resulting in good results. The evaluation results are shown in Table 1.

[0100] [Example 7] Following the procedure of Example 1, Nikkan Industries' SAFN (storage modulus after curing: 400 MPa) was laminated or directly applied and dried at 100°C on the surface of a polyethylene terephthalate polarizing film [glass transition temperature 70.7°C] (thickness 100 to 140 microns) to obtain a functional layer with a curable adhesive layer AD2. Furthermore, the material was changed to lens material 2, and a substrate (lens) with a diameter of 75φ, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. The adhesive layer was cured at 90° C. for 2 hours in the same manner as in Example 1, but no peeling or displacement of the functional layer was observed. Furthermore, no peeling or displacement was observed even after annealing at 120° C. for 2 hours. Next, the lenses with the functional layer were edged in dry mode with a width of 49 mm and a height of 28 mm using a Nidek edger (edging machine) (LEX-1000), and the adhesion between the functional layer and the lens (substrate) was evaluated. There was no peeling between the functional layer and the substrate, and no processing residue was found on the functional layer, resulting in a good result. The evaluation results are shown in Table 1.

[0101] [Comparative Example 1] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. A commercially available acrylic adhesive (manufactured by Fujimori Kogyo Co., Ltd.) with an adhesive layer thickness of 100 microns (tackiness 11.7 degrees, storage modulus 0.03 MPa) was used as the adhesive layer AD2-1, and a functional layer with an adhesive layer was obtained in the same manner as in Example 1, except that lamination was performed at room temperature.Then, the functional layer with an adhesive layer was obtained, and the functional layer was obtained by stretching and attaching it to the substrate of lens material 2. Since the adhesive layer does not require thermal curing, we annealed it at 120°C for two hours, and the surrounding area had almost completely peeled off, leaving only a central area about 5 cm in diameter. Next, the lens with the functional layer was edged in dry mode using a Nidek edger (edging machine) (LEX-1000) to a width of 40 mm and height of 28 mm, resulting in chuck marks for mounting the lens on the device for grinding. The evaluation results are shown in Table 1.

[0102] [Comparative Example 2] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. A commercially available acrylic adhesive (manufactured by Nitto Denko Corporation) (tackiness 28.9 degrees, storage modulus 0.03 MPa) with an adhesive layer thickness of 25 microns was used as the adhesive layer AD2-1, and a functional layer with an adhesive layer was obtained in the same manner as in Example 1, except that lamination was performed at room temperature.Then, the functional layer with an adhesive layer was obtained, and the functional layer was obtained by stretching and attaching it to the substrate of lens material 2. Since the adhesive layer does not require thermal curing, we annealed it at 120°C for two hours, and the surrounding area had almost completely peeled off, leaving only a central area about 3 cm in diameter. The evaluation results are shown in Table 1.

[0103] [Comparative Example 3] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. As the curable adhesive layer AD2, epoxy-based liquid adhesive for optical components GA-R-1 / GA-H-1 (manufactured by Canon) (storage modulus after curing: 5 GPa; in an uncured state, a 32 g steel ball would sink into the liquid adhesive, so tackiness cannot be evaluated by the above method; and when the functional layer on which the liquid adhesive is disposed is made parallel to the vertical direction at 25°C, the liquid adhesive will flow and at least a portion of it will detach from the functional layer) was used, and the functional layer used in Example 1 was only bent, bonded to the substrate, and cured at 80°C for 3 hours to obtain a lens with a functional layer. The functional layered lens was edged to a width of 40 mm and a height of 28 mm in dry mode using a Nidek edger (edge ​​processing machine) (LEX-1000). Peeling occurred between the functional layer and the substrate, and processing residue was observed. The evaluation results are shown in Table 1. In Table 1 and Table 2 described later, the adhesives described as sheet-like adhesives refer to adhesives that, in an uncured state arranged on a functional layer or substrate, do not flow significantly and the components of the sheet-like adhesive do not become liquid and fall off from the functional layer or substrate even when maintained parallel to the vertical direction at 25°C for about 20 minutes.

[0104] [Table 1]

[0105] [Example 8] A functional layer with a curable adhesive layer AD2 was prepared in the same manner as in Example 1, and then an adhesive for thermosetting sheets (Nikaflex(R) SAFS manufactured by Nikkan Industries Co., Ltd.) was laminated or applied to the back side of the functional layer on which AD2 was located, to prepare a functional layer with an adhesive layer comprising a curable adhesive layer AD1, a functional layer, and an adhesive layer AD2 in that order. The functional layer was attached to a substrate (lens) in the same manner as in Example 1 and cured at 90° C. for 2 hours to produce a lens with a functional layer, and a protective layer was formed on the surface of the cured adhesive layer AD1-1 by the following method: 2 g of an epoxy acrylic hard coat agent (manufactured by Daicel Corporation, 163) was placed on the concave surface of a glass mold having a concave surface matching the curve of the convex surface of the lens with a functional layer, and the lens with a functional layer was placed on top of it, pressed against it, and inverted, and a protective layer was formed on the concave surface of the glass mold by the following method. 2 The glass mold was then released to produce a lens with a functional layer in which a protective layer having a thickness of 0.3 mm was formed on the adhesive layer AD1-1. In this manner, a lens with a protective layer and a functional layer (laminate) having a protective layer, an adhesive layer AD1-1, a functional layer, an adhesive layer AD2-1, and a substrate in this order was obtained. The laminate was annealed at 120° C. for 2 hours in the same manner as in Example 1. No peeling or other problems were observed on the periphery. The peripheral machining using a curve generator in the same manner as in Example 1 was also satisfactory with almost no residual machining. When edging was performed in a dry mode in the same manner as in Example 1, the protective layer and the functional layer did not peel off, and there was no residual processing in the functional layer, which was satisfactory.

[0106] [Example 9] A functional layer with an adhesive layer, which had a curable adhesive layer AD1, a functional layer, and a curable adhesive layer AD2 in this order, was produced in the same manner as in Example 7. The substrate (lens) was produced by drying pellet-shaped polycarbonate using a known method, followed by injection molding to produce a polycarbonate substrate (lens) with a diameter of 75φ, a thickness of 2 mm at the lens center, and a curvature radius of 88 mm. The functional layer was laminated to a polycarbonate substrate (lens) while being spread in the same manner as in Example 1, and cured at 90° C. for 2 hours to produce a lens with a functional layer. An epoxy acrylic hard coat agent (manufactured by Daicel Corporation, 163) was applied to the surface of the cured adhesive layer AD1-1 by spin coating at a rotation speed of 800 rpm, and 1000 mJ / cm 2 The coating was cured by irradiating UV at an irradiation intensity of 1000 nm to form a protective layer of 0.1 mm, and a lens with a protective layer and a functional layer (laminate) was obtained which had, in that order, a protective layer, an adhesive layer AD1-1, a functional layer, an adhesive layer AD2-1, and a substrate (lens). Next, the laminate was edged in dry mode with a width of 49 mm and a height of 28 mm using a Nidek edger (edging machine) (LEX-1000), and the adhesion between the functional layer and the lens (substrate) was evaluated. There was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and no processing residue was found on the functional layer, so the results were excellent.

[0107] [Example 10] A substrate was prepared in the same manner as in Example 1, and a functional layer with an adhesive layer, which had a curable adhesive layer AD1, a functional layer, and a curable adhesive layer AD2 in that order, was prepared in the same manner as in Example 7. The substrate and the functional layer were laminated while being stretched, and cured at 90°C for 2 hours to prepare a substrate (lens) with a functional layer and an adhesive layer AD1-1. A protective layer was formed on the surface of the cured adhesive layer AD1-1 by the following method: 2 g of urethane acrylate (V-4001EA, manufactured by DIC Corporation) was placed on the concave surface of a glass mold having a concave surface that matches the curve of the convex surface of the lens with a functional layer, the lens with a functional layer was placed on top of it, pressed against it, and inverted, and then 1000 mJ / cm 2The glass mold was released to produce a lens with a protective layer and a functional layer (laminate) in which a protective layer with a thickness of 0.5 mm was formed on the adhesive layer AD1-1. This laminate was annealed at 120° C. for 2 hours in the same manner as in Example 1. No peeling or other problems were observed on the outer periphery. The peripheral machining using a curve generator in the same manner as in Example 1 was also satisfactory with almost no residual machining. Dry mode edging was carried out in the same manner as in Example 1, and the results were good, with no peeling of the protective layer or functional layer, and no residual processing of the functional layer.

[0108] [Example 11] The procedure of Example 1 was followed except that the material was changed to Lens Material 2, and a base material (lens) having a diameter of 75 mm, a thickness of 2 mm at the lens center, and a radius of curvature of 88 mm was produced according to a known production method. In addition, using a method similar to that of Example 7, a functional layer with an adhesive layer was prepared having a curable adhesive layer AD1, a functional layer, and a curable adhesive layer AD2 in that order, and this was stretched and bonded to a substrate, and cured at 90°C for 2 hours to produce a lens with a functional layer and adhesive layer AD1-1. A protective layer was formed on the surface of the adhesive layer AD1-1 of the lens with a functional layer with adhesive layer AD1-1 by the following method. A 0.5 mm spacer was placed on the outer periphery of the concave surface of a glass mold having a concave surface matching the curve of the convex surface of the lens with a functional layer, 4 g of lens material 2 was placed on the concave surface of this glass mold, the lens with a functional layer was placed on top of that, and the temperature was gradually raised from 30°C to 115°C over 12 hours as in Example 1 to harden, and the glass mold was released to produce a lens with a functional layer with a protective layer (laminate) in which a 0.3 mm thick protective layer was formed on the adhesive layer AD1-1. After curing, no peeling or misalignment of the functional layer was observed. Also, no peeling or misalignment was observed even after annealing at 120°C for 2 hours. Next, the laminate was edged in dry mode with a Nidek edger (edge ​​processing machine) (LEX-1000) at a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and there was no residual processing of the functional layer, resulting in a good result.

[0109] [Example 12] The curable adhesive layer AD1 in Example 11 was changed from Nikkan's SAFS to Sotek's Assist 7M (urethane elastomer-based thermosetting resin), and the curable adhesive layer AD2 was changed to Nikkan's SAFN (urethane-based), to prepare a lens with a protective layer as follows. The functional layer with the curable adhesive layer AD2 (functional layer with 8μm of Nikkan SAFN laminated on one side) was attached while being heated and bent as in other examples so that the AD2 side was the convex side of the lens substrate, and the AD2 layer was heat cured as in other examples. Next, Assist 7M was diluted to 6wt% with toluene, and 10μm was applied to the surface of the functional layer by spin coating, dried, and cured at 90℃ for 120 minutes to prepare a lens with a functional layer with adhesive layer AD1-1, in which adhesive layer AD1-1, functional layer, adhesive layer AD2-1, and lens substrate were laminated in this order. A protective layer of lens material 2 was formed on the surface of adhesive layer AD1-1 of the lens with functional layer having adhesive layer AD1-1 by the following method in the same manner as in Example 11. Lens material 2 was placed on the outer periphery of the concave surface of a glass mold having a concave surface matching the curve of the convex surface of the lens with functional layer, a 0.5 mm spacer was placed, 4 g of lens material 2 was placed on the concave surface of this glass mold, the lens with functional layer was placed on top of that, and the temperature was gradually raised from 30°C to 115°C over 12 hours in the same manner as in Example 1 to harden, and the glass mold was released to produce a lens with functional layer (laminate) in which a 0.3 mm thick protective layer was formed on adhesive layer AD1-1. After curing, no peeling or misalignment of the functional layer was observed. Also, no peeling or misalignment was observed even after annealing at 120°C for 2 hours. Next, the lens with the functional layer was edged in dry mode with a Nidek edger (edging machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and no residual processing of the functional layer, and the results were good.

[0110] [Example 13] The adhesive layer AD1 in Example 11 was changed from Nikkan SAFS to Sotec Assist 7M (urethane elastomer thermosetting resin), and a lens substrate with a protective layer was prepared as follows. A functional layer with a curable adhesive layer AD2 (a functional layer with 25 μm of Nikkan Corporation's Nikkaflex SAFS laminated on one side) was heated and bent as in the other examples so that the AD2 side was on the convex side of the lens substrate, and the AD2 layer was heat-cured as in the other examples. Assist 7M was then diluted to 6 wt% with toluene and coated at 10 μm using a spin coating method, dried, and cured at 90°C for 120 minutes to produce a lens with a functional layer with adhesive layer AD1-1, in which adhesive layer AD1-1 (a layer formed by curing adhesive layer AD1), functional layer, adhesive layer AD2-1, and lens substrate were laminated in that order. The surface of the adhesive layer AD1-1 of the functional layer-attached lens having the adhesive layer AD1-1 was coated with the and Similarly, a protective layer of lens material 2 was prepared by the following method: A 0.5 mm spacer was placed on the outer periphery of the concave surface of a glass mold having a concave surface matching the curve of the convex surface of the lens with a functional layer, 4 g of lens material 2 was placed on the concave surface of this glass mold, the lens with a functional layer was placed on top of that, and the temperature was gradually raised from 30°C to 115°C over 12 hours as in Example 1 to harden it, and the glass mold was released to prepare a lens with a functional layer (laminate) in which a 0.3 mm thick protective layer was formed on the adhesive layer AD1-1. After curing, no peeling or misalignment of the functional layer was observed. Also, no peeling or misalignment was observed even after annealing at 120°C for 2 hours. Next, the laminate was edged in dry mode with a Nidek edger (edge ​​processing machine) (LEX-1000) at a width of 49 mm and a height of 28 mm. As a result, there was no peeling between the protective layer and the functional layer, or between the functional layer and the substrate, and there was no residual processing of the functional layer, resulting in a good result.

[0111] [Comparative Example 4] Lens material 2 in Example 11 was changed to Beamset 575B manufactured by Arakawa Chemical Industries, Ltd., and applied by spin coating at 1000 mJ / cm 2A functional layer-equipped lens (laminate) having a protective layer formed thereon was produced in the same manner as in Example 11, except that the protective layer was cured by irradiating UV at an integrated amount of 0.3 mm. The hardened protective layer had several cracks. The laminate was edged in dry mode with a Nidek edger (edge ​​processing machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, chipping occurred on the outer periphery of the protective layer, peeling occurred, and some of the functional layer remained unshaved.

[0112] [Comparative Example 5] Lens material 2 in Example 12 was changed to ThreeBond 3121D, and applied by spin coating at 3000 mJ / cm 2 A functional layer-equipped lens (laminate) having a protective layer formed thereon was produced in the same manner as in Example 12, except that the protective layer was cured by irradiating UV at an integrated amount of 0.3 mm. The hardened protective layer had several cracks. The laminate was edged in dry mode with a Nidek edger (edge ​​processing machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, the remaining protective layer and functional layer escaped to the convex side of the lens on the periphery and peeled off.

[0113] [Comparative Example 6] Lens material 2 in Example 12 was changed to ThreeBond 3043B, and applied by spin coating at 3000 mJ / cm 2 A functional layer-equipped lens (laminate) having a protective layer formed thereon was produced in the same manner as in Example 12, except that the protective layer was cured by irradiating UV at an integrated amount of 0.3 mm. The hardened protective layer had several cracks. The laminate was edged in dry mode with a Nidek edger (edge ​​processing machine) (LEX-1000) to a width of 49 mm and a height of 28 mm. As a result, the remaining protective layer and functional layer escaped to the convex side of the lens at the periphery and peeled off.

[0114] [Table 2]

[0115] This application claims priority based on Japanese Patent Application No. 2018-180714, filed on September 26, 2018, the disclosure of which is incorporated herein in its entirety.

Claims

1. A functional layer; A curable adhesive layer AD2 disposed on at least a portion of the surface of the functional layer; Equipped with The curable adhesive layer AD2 satisfies all of the following requirements (1), (2), and (4), The curable adhesive layer AD2 is a polyester-based thermosetting sheet-like adhesive or a urethane-based thermosetting sheet-like adhesive. (1) At 25° C., a 32 g steel ball was placed on the adhesive surface of the curable adhesive layer AD2 on a glass plate, and after holding the ball for 10 seconds, the glass plate was gradually tilted until the angle at which the steel ball began to roll was 5 degrees or less. (2) After curing at 90° C. for 2 hours, the ratio (b / a) of the amount of plastic deformation b to the amount of elastic deformation a at 25° C. under a load of 0.1 mN is 1.5 or more and 50 or less. (4) A storage modulus at 25°C after curing at 90°C for 2 hours is 10 MPa or more and 1000 MPa or less.

2. The adhesive layer-attached functional layer according to claim 1 , wherein the curable adhesive layer AD2 satisfies the following requirement (3). (3) After curing at 90°C for 2 hours, the dynamic hardness (DHT115-2) after unloading a 0.1 mN load at 25°C is 0.01 to 5000.

3. The functional layer with an adhesive layer according to claim 1 or 2, wherein the amount of plastic deformation b is greater than 0 and is 1 or less.

4. 4. The functional layer with an adhesive layer according to claim 1, wherein the functional layer comprises a polymer layer having a glass transition temperature and a softening point temperature of 0° C. or higher and a thickness within the range of 1 μm to 1 mm.

5. The functional layer with an adhesive layer according to claim 4 , wherein the polymer layer has at least one property selected from the group consisting of polarizing properties, specific wavelength absorption properties, light control properties, and color control properties.

6. The adhesive layer-attached functional layer according to claim 1 , wherein the thickness of the curable adhesive layer AD2 is less than 100 μm.

7. The adhesive layer-attached functional layer according to claim 1 , wherein the curable adhesive layer AD2 further satisfies the following requirements: (5) The refractive index (JIS K7142) after curing is 1.45 or more.

8. The functional layer with an adhesive layer according to claim 4 or 5, wherein the polymer layer is a substantially uniaxially stretched film.

9. The adhesive layer-attached functional layer according to claim 8 , wherein the polymer layer is a polarizing film containing polyethylene terephthalate.

10. A functional layer; Adhesive layer AD2-1; A substrate; In this order, The adhesive layer AD2-1 is disposed at least in a portion between the opposing surfaces of the functional layer and the base material, and the adhesive layer satisfies all of the following requirements (i) and (iii): The substrate with a functional layer, wherein the adhesive layer AD2-1 is a polyester-based thermosetting sheet-like adhesive or a urethane-based thermosetting sheet-like adhesive. (i) The ratio (b / a) of the amount of plastic deformation b to the amount of elastic deformation a at 25° C. and a load of 0.1 mN is 1.5 or more and 50 or less. (iii) A storage modulus at 25° C. of 10 MPa or more and 1000 MPa or less.

11. The substrate with a functional layer according to claim 10, wherein the adhesive layer AD2-1 satisfies the following requirement (ii): (ii) Dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25° C. is 0.01 to 5000

12. A protective layer; A functional layer; Adhesive layer AD2-1; A substrate; In this order, The adhesive layer AD2-1 is disposed at least in a portion between the opposing surfaces of the functional layer and the base material, and the protective layer satisfies all of the following requirements (a), (b), and (c), and the adhesive layer AD2-1 satisfies all of the following requirements (i) and (iii), The adhesive layer AD2-1 is a polyester-based thermosetting sheet adhesive or a urethane-based thermosetting sheet adhesive, The protective layer is a laminate containing at least one curable resin selected from an epoxy-based curable resin, a urethane acrylate-based curable resin, an epoxy acrylate-based curable resin, a urethane-based curable resin, an acrylic-based curable resin, and a thiourethane-based curable resin. (a) Thickness is 10 μm to 1 mm (b) At 25° C., the ratio (b / a) of the amount of plastic deformation b to the amount of elastic deformation a under a load of 0.1 mN is 0.1 to 10 (c) Dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25°C is 400 to 3000 (i) The ratio (b / a) of the amount of plastic deformation b to the amount of elastic deformation a at 25° C. and a load of 0.1 mN is 1.5 or more and 50 or less. (iii) A storage modulus at 25° C. of 10 MPa or more and 1000 MPa or less.

13. The laminate according to claim 12 , wherein the protective layer satisfies the following requirement (d): (d) Pencil hardness HB to 9H

14. Further, an adhesive layer AD1-1 is provided between the protective layer and the functional layer, The laminate according to claim 12 or 13, wherein the adhesive layer AD1-1 satisfies the following requirement (i): (i) The ratio (b / a) of the amount of plastic deformation b to the amount of elastic deformation a at 25° C. and a load of 0.1 mN is 0.01 to 100.

15. The laminate according to claim 14, wherein the adhesive layer AD1-1 satisfies the following requirement (ii): (ii) Dynamic hardness (DHT115-2) after unloading a load of 0.1 mN at 25° C. is 0.01 to 5000

16. The laminate according to claim 14 or 15, wherein the adhesive layer AD1-1 satisfies the following requirement (iii): (iii) A storage modulus at 25° C. of 0.5 MPa or more and 1000 MPa or less.

17. 17. An optical part comprising the substrate with a functional layer according to claim 10 or 11, or the laminate according to any one of claims 12 to 16, wherein the substrate is a lens having a refractive index of 1.49 or more.

18. 18. The optical component of claim 17, wherein the adhesive layer AD2-1 contacts at least a portion of the surface of the lens.

19. 19. The optical component according to claim 17 or 18, wherein the lens comprises one or more materials selected from the group consisting of polycarbonate resin, polyester resin, polyester copolymer, polyamide resin, polyimide resin, poly(meth)acrylate resin, polyolefin resin, polyureaurethane resin, poly(thio)urethane resin, polysulfide resin, poly(meth)(thio)acrylate resin, allyl diglycidyl carbonate resin, and inorganic glass.

20. The optical component according to claim 19 , wherein the functional layer is a polarizing lens having polarizing properties.

Citation Information

Patent Citations

  • Polarizing lens

    JP1997258009A

  • Molded polyethylene terephthalate polarizer film for incorporation into optical quality plastic parts

    JP2003533719A

  • Polarizing optical element with polarizing film and method for manufacturing such element

    JP2009527783A

  • Polarizing element

    JP2011145513A

  • Colored plastic lens, and manufacturing method for the same

    JP2014092580A

Cited By

  • Functional layer with adhesive layer, laminate and use thereof

    JP2023054001A